Effects of promoting longer-term and exclusive breastfeeding on adolescent adiposity, blood pressure, and longitudinal growth trajectories: evidence from the PROBIT cluster-randomized trial - Martin, Richard M (JAMA Pediatr, 2017)
IMPORTANCE: Evidence that breastfeeding reduces child obesity risk and lowers blood pressure (BP) is based on potentially confounded observational studies. OBJECTIVE: To investigate the effects of a breastfeeding promotion intervention on adiposity and BP at age 16 years, and on longitudinal growth trajectories from birth. DESIGN: Cluster-randomized Promotion of Breastfeeding Intervention Trial, allocated in 1996–1997 into intervention (n=16) or control arms (n=15). SETTING: Belarusian maternity hospitals and affiliated polyclinics. PARTICIPANTS: 17,046 breastfeeding mother-infant pairs, of whom 13,557 (79.5%) children were followed-up at 16. INTERVENTION: Breastfeeding promotion, modeled on the Baby-Friendly Hospital Initiative. MAIN OUTCOME MEASURES: Body mass index (BMI); fat and fat-free mass indices (FMI and FFMI) and percent body fat from bioimpedance; waist circumference; overweight and obesity; height; BP; and longitudinal growth trajectories. The primary analysis was modified intention-to-treat (without imputation for losses to follow-up), accounting for within-clinic clustering. RESULTS: The intervention substantially increased breastfeeding duration and exclusivity compared with the control arm (exclusively breastfed: 45% vs 6% at 3 months, respectively). Mean differences at 16 years between intervention and control groups were: 0.21 kg/m(2) (95%CI:0.06, 0.36) for BMI; 0.21 kg/m(2) (−0.03, 0.44) for FMI; 0.00 kg/m(2) (−0.21, 0.22) for FFMI; 0.71% (−0.32, 1.74) for percent body fat; −0.73 cm (−2.48, 1.02) for waist circumference; 0.05 cm (−0.85, 0.94) for height; −0.54 mmHg (−2.40, 1.31) for systolic BP; and 0.71 mmHg (−0.68, 2.10) for diastolic BP. The odds ratio for overweight/obesity (BMI≥85(th) vs <85(th) percentile) was 1.14 (1.02, 1.28) and for obesity (BMI≥95(th) vs <95(th) percentile) was 1.09 (0.92, 1.29). The intervention resulted in a more rapid rate of gain in post-infancy height (1 to 2.8 years), weight (2.8 to 14.5 years), and BMI (2.8 to 8.5 years) compared to the control arm. The intervention had little effect on BMI z-score changes after 8.5 years. CONCLUSIONS: A randomized intervention that increased the duration and exclusivity of breastfeeding did not lower adolescent obesity risk or BP. On the contrary, the prevalence of overweight/obesity were higher in the intervention arm. All mothers initiated breastfeeding, so findings may not apply to comparisons of the effects of breastfeeding versus formula-feeding.